Mathematical Communication Ability Based On Cognitive Style in PBL With Tutor Feedback Assisted by Triangle Calculator - Fadillah, Lukky; Kartono, Kartono; Supriyadi, Supriyadi (Unnes Journal of Mathematics Education Research, 2020)
This research’s purposes are to (1) verify the effectiveness of Problem Based Learning (PBL) with tutor feedback assisted by triangle calculator towards the mathematical communication ability of 10th grade students, and (2) describe it based on cognitive style. This research used mixed method with concurrent embedded type as a methodology. The population of this research are 10th grade students of the Senior High School 1st Kadugede Kuningan (2018/2019). The result shows that (1) PBL with tutor feedback assisted by triangle calculator is effective toward the mathematical communication ability, and (2) the depiction of the mathematical communication ability based on Field Dependent (FD) cognitive style is able to complete four indicators, but unable to illustrate the image well and compete it correctly, on the other side based on Field Intermediate (FDI) cognitive style it is able to complete four indicators but not in a correct way, whilst based on Field Independent (FI) cognitive style it is able to complete for indicators correctly.